2010
DOI: 10.1177/1538574410362922
|View full text |Cite
|
Sign up to set email alerts
|

Basic Science Review: Statin Therapy-Part I: The Pleiotropic Effects of Statins in Cardiovascular Disease

Abstract: 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG CoA-reductase) inhibitors, otherwise known as statins, are currently the medical treatment of choice for hypercholesterolemia. Hypercholesterolemia is a known risk factor for cardiovascular disease, and statin therapy has led to a significant reduction in morbidity and mortality from adverse cardiac events, stroke, and peripheral arterial disease. In addition to achieving a therapeutic decrease in serum cholesterol levels, statin therapy appears to promote o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 117 publications
1
114
0
1
Order By: Relevance
“…SIM is widely used for cardiovascular diseases [40] . However, statins have pleiotropic therapeutic effects including vasodilatory, antithrombotic, antioxidant, anti-inflammatory, and immunosuppressive actions [41] . Mundy was first reported statins as potent stimulators of bone formation invitro.…”
Section: Discussionmentioning
confidence: 99%
“…SIM is widely used for cardiovascular diseases [40] . However, statins have pleiotropic therapeutic effects including vasodilatory, antithrombotic, antioxidant, anti-inflammatory, and immunosuppressive actions [41] . Mundy was first reported statins as potent stimulators of bone formation invitro.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolaemia is a known risk factor for cardiovascular disease, and statin therapy has led to a significant reduction in morbidity and mortality from adverse cardiac events, stroke, and peripheral arterial disease [140,141]. Statins block the enzyme necessary for the production of L-mevalonate, an intermediary product in cholesterol synthesis.…”
Section: Statinsmentioning
confidence: 99%
“…27) it reported that the effect of statins decreasing the number of macrophages is associated with decreased VCAM-1 expression, higher VSMC content in the plaque. [28][29][30] Our data show that the effects of 3,4-DHAP are similar to simvastatin, decreasing the expressions of VCAM-1 mRNA and protein and the number of macrophage, and increasing VSMCs in rabbit aortic plaques.…”
Section: 4-dhap Attenuates Aortic Plaque Vulnerability By Decreasinmentioning
confidence: 54%